REGULATORY FRAMEWORK AND CHALLENGES IN THE DISTRIBUTION OF HERBAL MEDICINES IN INDONESIA - Violeta Mashary (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Traditional herbal medicine, known as jamu in Indonesia, has long been part of the cultural and healthcare practices in Southeast Asia. This study aims to explore the role of governmental legal instruments in enhancing the sustainability and global promotion of jamu as a valuable national heritage. Using a qualitative descriptive method, the study analyzes primary and secondary legal sources, including Presidential Regulation Number 54 of 2023 on the Development and Utilization of Herbal Medicine. The regulation signifies the Indonesian government's commitment to preserving and developing jamu following its recognition as an intangible cultural heritage by UNESCO on December 6, 2023. The findings reveal that the regulation provides a legal foundation to optimize the benefits of jamu, prevent misuse, and promote sustainable development of traditional herbal practices. However, the research suggests that further efforts are needed to build a broader movement for public awareness, encourage the regeneration of herbal practitioners, and utilize jamu as a soft diplomacy tool to introduce Indonesian herbal culture globally. By strengthening legal support and public engagement, jamu can be positioned not only as a traditional remedy but also as a strategic national asset contributing to health, cultural identity, and international recognition.